A case study of Malaysia: the impact of exchange rate changes on the price of imported product and on trade (1996-2005) / Noorhabibah Mohd Harudin - Mohd Harudin, Noorhabibah (2007)
This study is identifying the correlation between exchange rate and the price of imported product. It is also considering the effect on the changes or movement of exchange rate to trade of imported product. Furthermore, this research also examines the way that exchange rate can influencing the trade flows of imported product. The data for this research is mostly based on the BNM Annual Report and BNM and BNM Monthly Statistical Bulletin. This study also have concentrated on three indicators, which are exchange rate, total price for imported product in Malaysia and trade balance from year 1996 to 2005 that base on yearly basis. This study will use the methods that come from Excel and SPSS. The methods that will be use for this research are the Simple Linear Regression, and Determination of Coefficient. From the finding result in this research, there have show that the exchange rate is really can effect the import price but it is not strongly effect the trading of imported product. As a conclusion, it means that the exchange rate have the impact on the price imported product and import trading.